A rare case of concomitant hypo-hyperdontia in identical twins - Sharma A (Wolters Kluwer Medknow Publications, 2008)
Concomitant hypodontia and hyperdontia is a rare condition of unknown etiology. One such case of occurring in identical twins in mixed dentition is presented and discussed. A sibling, especially a twin of an affected patient, should be suspected of having a similar problem, even if he or she is asymptomatic. Genetic factors probably play an important etiological role in the co-occurence of partial anodontia and supernumerary teeth.